Chemical modification of biochar’s functional groups enhances phosphate and arsenite adsorption - Md Rayhan Ahmed; Shamim Mia; Md. Abdus Sattar; M. M. Masud; S. M. Mahabubul Alam; Sohela Akter; Md. Sharif Mia; Sanjida Aktar (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Anionic arsenic (As) species and phosphate often show similar behavior in soils. Bioavailability of these anionic species has a significant implication for crop production and soil health. Biochar (BC) is considered an effective amendment for managing these anionic species. This study aims to evaluate how surface-modified biochars influence phosphate and arsenite adsorption. Biochars with a range of functionalities were produced using mineral doping, and chemical oxidation with hydrogen peroxide. These biochars were then characterized using different chemical techniques, including FTIR. Next, a phosphorus adsorption study was conducted with fresh, mineral-doped and chemically oxidized biochars. A desorption study was also conducted to understand the strength of sorption. Moreover, an adsorption study was carried out using three different biochars fresh, oxidized, and doped in interaction with As. Our results showed that chemical oxidation increased oxygen-containing functional groups while mineral impregnation decreased their presence, resulting in a reduction in cation exchange capacity. As a result, phosphate adsorption was significantly higher with mineral- doped biochar (2.5 mg g-1 biochar) than in fresh biochar (2.2 mg g-1 biochar) treatment. The strength of binding was higher for positively charged biochars. Similar to phosphate, the As adsorption was also higher in the doped biochar (~0.50 mg g-1 biochar) than oxidized biochar (0.20 mg g-1biochar). Surprisingly, the As adsorption was higher in the oxidized BC than fresh BC possibly due to its co-adsorption with cations. Altogether, our results suggest that biochar with positive surfaces could strongly bind negatively charged ions from aqueous solutions and soils.